2015
DOI: 10.1089/chi.2014.0117
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverages and Obesity among Children and Adolescents: A Review of Systematic Literature Reviews

Abstract: Background: The prevalence of overweight and obesity among children and adolescents has increased worldwide and has reached alarming proportions. Currently, sugar-sweetened beverages (SSBs) are the primary source of added sugar in the diet of children and adolescents. Contradictive findings from studies and reviews have fueled an endless debate on the role of SSBs in the development of childhood obesity.Methods: The primary aim of the present review of reviews was to assess how review-and study-level methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(175 citation statements)
references
References 46 publications
(154 reference statements)
7
139
3
3
Order By: Relevance
“…Adjustment for total energy intake is conducted due to controlling for confounding variables, for reducing variation, and for predicting the effect of the intervention. However, as SSBs add calories to the diet, it has also been discussed that the adjustment for total energy intake might lead to an underestimation of the effect of SSBs on body weight as total energy intake mediates the association between SSBs and body weight [15]. In our systematic review, about half of the prospective cohort studies in children and also about half in adults adjusted for energy intake, but no RCT adjusted for that.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Adjustment for total energy intake is conducted due to controlling for confounding variables, for reducing variation, and for predicting the effect of the intervention. However, as SSBs add calories to the diet, it has also been discussed that the adjustment for total energy intake might lead to an underestimation of the effect of SSBs on body weight as total energy intake mediates the association between SSBs and body weight [15]. In our systematic review, about half of the prospective cohort studies in children and also about half in adults adjusted for energy intake, but no RCT adjusted for that.…”
Section: Discussionmentioning
confidence: 90%
“…This suggests an independent effect of SSBs, even though residual confounding by unmeasured or poorly measured factors cannot be ruled out. Total energy adjustments might influence the direction of the relationship between SSB intake and body weight measures and might change research results, which was discussed in a review in 2015 [15]. Adjustment for total energy intake is conducted due to controlling for confounding variables, for reducing variation, and for predicting the effect of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review concluded that intake of free sugars or sugar sweetened beverages was a determinant of body weight, with increased sugar intake leading to weight gain and inversely [Te Morenga et al, 2012]. Evidence from other systematic reviews and meta-analyses also suggest a direct association between intake of sugarsweetened beverages and weight gain, overweight and obesity [Keller, and Bucher Della Torre, 2015;Malik et al, 2013].…”
mentioning
confidence: 99%
“…In 2015, Keller and Bucher Della Torre (2015) examined 13 systematic reviews on the relationship between SSBs and obesity in children. The quality of the included studies was low to moderate, and 9 indicated a positive association between SSBs and obesity.…”
Section: Sugar-sweetened Beverages and Obesity Riskmentioning
confidence: 99%